HUBUNGAN PENGETAHUAN IBU TERHADAP KEJADIAN STUNTING DI PUSKESMAS SEPATAN, KABUPATEN TANGERANG: THE RELATIONSHIP BETWEEN MATERNAL KNOWLEDGE AND STUNTING INCIDENCE AT THE SEPATAN HEALTH CENTER, TANGERANG REGENCY, 2025 - Hadi Nugroho; Fierdania Yusvita; Gunita Fauziati (Politeknik Kesehatan Kemenkes RI Jakarta I, 2026)
Stunting is a chronic nutritional problem affecting children's growth, cognitive development, and human resource quality. Maternal knowledge is a key factor in stunting prevention through appropriate feeding and child-rearing practices. This study aimed to analyze the association between maternal knowledge and stunting incidence in children under five at Puskesmas Sepatan, Tangerang Regency, and to quantify the adjusted risk through multivariate analysis while controlling for confounders. A case-control design was used with 80 respondents (40 stunting cases and 40 non-stunting controls) drawn from the same source population and selected purposively. Data were collected through structured interviews using a validated questionnaire and height-for-age measurements based on WHO standards. Bivariate analysis used the Chi-square test and multivariate analysis used binary logistic regression with backward elimination and confounding assessment. Bivariate results showed a significant association between maternal knowledge and stunting (p=0.001); the proportion of mothers with poor knowledge was higher in the case group (62.5%) than the control group (25.0%). Multivariate modeling, controlling for maternal education and maternal age as confounders, showed that mothers with poor knowledge had a 7.93-fold higher risk of having a stunted child (adjusted OR=7.93; 95% CI: 2.36–26.55; p<0.001). The model yielded a Nagelkerke R Square of 0.381 and was declared fit (Hosmer-Lemeshow p=0.761). Maternal knowledge is the modifiable determinant most strongly associated with stunting. Improving maternal knowledge through continuous nutrition counseling at the health center should be prioritized as a stunting prevention strategy